Muzyka jako czynnik rozwoju wyobraźni dziecka w wieku przedszkolnym - implikacje teoretyczne = Music as a factor favoring the development of imagination of pre-school children - theoretical implications - Majzner, Rafał (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The author presents the definition of imagination, its types and directions of development. The purpose of the following article is to prezent the essence of the influence of music on a preschool child targeting at the development of the child`s imagination. The presented theoretical reflections are an attempt to justify the thesis saying that various forms of musical interactions consciously applied in kindergarten contain enormous educational potential, and are a factor favoring the development of the child`s personality.
Keywords: wyobraźnia; muzyka; dziecko; formy wychowania muzycznego; imagination; music; child; forms of musical education